POTENTIAL FOR THE DEVELOPMENT OF AGRITOURISM IN THE FOOD SUPPLY ZONE OF THE REPUBLIC OF KAZAKHSTAN, NUR-SULTAN CITY - Gulnara Sh. OSPANOVA; Abdimazhit A. SAIPOV; Aigul M. SERGEYEVA; Kuat T. SAPAROV; Miroslava Zh. OMIRZAKOVA; Raushan D. NURYMOVA (Geo Journal of Tourism and Geosites, 2022)
One of the important situations is the agricultural production and sustainable development of the suburban zone of the city of Nur-Sultan, the organization of agritourism. In this regard, this study examines the development of agritourism in the food supply zone of the city Nur – Sultan. The object of the study is the suburban areas of Nur-Sultan. The purpose of the article is to identify the problem of formation and development of agrotourism in the agro-food complex of the metropolis suburban area and to propose a model for the development of the food supply zone of the city of Nur-Sultan. The main research method is a spatial analysis of the location of administrative regions in the food supply zone. In the course of the study, the article gives an integral assessment of the tourism potential of the regions of the food supply zone and identifies priority areas for the development of agricultural routes.